Case Report: A case of neonatal osteogenesis imperfecta: navigating critical care and early fracture management through multidisciplinary collaboration - Xie, Haoqiang; He, Fuzhen; Wu, Fengmin; Xu, Weisen; Li, Ning; He, Xiaoguang (Frontiers in Pediatrics, 2025)
BackgroundOsteogenesis Imperfecta (OI) poses a unique challenge in pediatric trauma and critical care, where the fragility of bone intersects with life-threatening systemic complications, such as neonatal respiratory failure. The early postnatal period is particularly precarious, demanding a delicate balance between life support and fracture prevention.Case presentationA 9-day-old male neonate with prenatally diagnosed COL1A2 (c.1459G > A, p.Gly487Arg) mutation was admitted to our NICU for respiratory distress and pneumonia. He was the progeny of a father with OI, delivered via cesarean section at 34 weeks due to fetal skeletal deformities.Management and outcomesA proactive, multidisciplinary team (MDT) protocol was immediately implemented, focusing on non-invasive respiratory support, meticulous handling to prevent iatrogenic injury, and optimized nutrition. This approach successfully resolved his respiratory failure without any new fractures during the NICU stay. However, on the 16th day post-discharge, the infant sustained a spontaneous fracture of the right proximal femur. This was managed conservatively with a Pavlik harness. Follow-up revealed rapid callus formation by day 52 and complete union by day 136, showcasing the characteristic hyperplastic healing pattern of OI.ConclusionThis case underscores that a coordinated MDT approach is vital for stabilizing critically ill neonates with OI. The occurrence of a fracture shortly after discharge highlights the transition to home care as a period of extreme vulnerability. Empowering families with comprehensive education and ensuring continuity of care are as crucial as in-hospital management for improving long-term outcomes in these fragile infants.